Tobacco use is associated with reduced amplitude and intensity dependence of the cortical auditory evoked N1-P2 component. - Jawinski, P.; Mauche, N.; Ulke, C.; Huang, J.; Spada, J.; Enzenbach, C.; Sander, C.; Hegerl, U.; Hensch, T. (Psychopharmacology (Berl), 2016)
RATIONALE: Tobacco use is linked to cerebral atrophy and reduced cognitive performance in later life. However, smoking-related long-term effects on brain function remain largely uncertain. Previous studies suggest that nicotine affects serotonergic signaling, and the intensity dependence (alias loudness dependence) of the auditory evoked N1-P2 potential has been proposed as a marker of serotonergic neurotransmission. OBJECTIVE: In the present study, we assesed the effects of chronic smoking on amplitude and intensity dependence of the auditory evoked N1-P2 potential. METHODS: Subjects underwent a 15-min intensity dependence of auditory evoked potentials (IAEP) paradigm. From N = 1739 eligible subjects (40-79 years), we systematically matched current smokers, ex-smokers, and never-smokers by sex, age, alcohol and caffeine consumption, and socioeconomic status. Between-group differences and potential dose-dependencies were evaluated. RESULTS: Analyses revealed higher N1-P2 amplitudes and intensity dependencies in never-smokers relative to ex- and current smokers, with ex-smokers exhibiting intermediate intensity dependencies. Moreover, we observed pack years and number of cigarettes consumed per day to be inversely correlated with amplitudes in current smokers. CONCLUSIONS: According to the IAEP serotonin hypothesis, our results suggest serotonin activity to be highest in current smokers, intermediate in ex-smokers, and lowest in never-smokers. To our knowledge, the present study is the first providing evidence for a dose-dependent reduction in N1-P2 amplitudes. Further, we extend prior research by showing reduced amplitudes and intensity dependencies in ex-smokers even 25 years, on average, after cessation. While we can rule out several smoking-related confounders to bias observed associations, causal inferences remain to be established by future longitudinal studies.
Keywords: Acoustic Stimulation; Adult; Aged; Arousal/drug effects; Auditory Cortex/*physiopathology; Cohort Studies; Dose-Response Relationship, Drug; Electroencephalography; Evoked Potentials, Auditory/*drug effects; Female; Humans; Male; Middle Aged; Serotonin/metabolism; Smoking/physiopathology; Socioeconomic Factors; Tobacco Use Disorder/*physiopathology